Factors affecting the graduation rate in the University of the Philippines College of Dentistry - Buenaventura, Criszel F.; Oliver, Ma. Cargielyn B.; Rebueno Santos, Jessica
Introduction. Doctor of Dental Medicine is a 6 year course. For the past 2005-2010 batches, 75 to 100% were delayed from graduation and thus took dentistry for more than 6 years. This is a high percentage compared to the less than 23% for those who graduated on time on the said batches. The attrition rate increases through time except with batch 2007 that broke the increase yet still after the said batch, the attrition rate still increases.
From the previous studies, the four major sectors that we found to be associated with the delayed graduation of the students at UPCD are: clinicians, patients, faculty and, the institution itself. For these four major categories, more factors may be identified that may be common across categories.
This study attempts to further investigate the possible factors related to each sector that contribute to the delayed graduation of students at UPCD. From 2005 to 2010, there were 165 delayed students compared with only 18 on-time students.
Methods. Participants of the study include 44 out of 76 clinicians, 17 out of 18 patients, 12 out of 15 faculty members and 9 out of 9 non-academic personnel. The number of participants was computed through the use of Statistics calculator of Epi info. Giving of survey questionnaires was our main data collection method. It was supported with a key informant interview and records review.
Results. Delay in graduation of UPCD clinicians at the new building is multifactorial. Six factors were identified to be associated with the clinicians and these include time management, attitude, clinical skills, patient management, financial resources and background in preclinical sciences. On the the other hand, faculty related factors were found to include time management, attitude, calibration and availability. For our third stakeholder, the patients, we were able to identify two factors associated with them--compliance and availability. The last stakeholder associated to the UPCD attrition rate is the institution. We were able to identify five factors related to our institution--faculty:clinician ratio, efficiency of facilities and supplies, economics, non-academic personnel and the number of clinicians in the clinics.
Conclusion. It can be concluded that there are several factors contributing to delay in graduation of UPCD clinicians. These factors are attributed to the clinicians, the faculty members, the patients and the institution. By informing the stakeholders regarding the factors that affect the graduation rate of the clinicians, these factors can be properly addressed, hence increase the number of clinicians graduating on time.
Keywords: College of Dentistry Graduates--Statistics.; University of the Philippines Manila